The Impact of Home Environment Factors on Academic Performance of Senior Secondary School Students in Garki Area District, Abuja - Nigeria - L. T. Dzever (University of Sofia, 2015)
The study examined the impact of home environment factors on the academic performance of public secondary school students in Garki Area District, Abuja, Nigeria. The stratified sampling technique was used to select 300 students from six public schools, while the simple random sampling technique was used to administer the questionnaire. The study utilized a descriptive survey research design for the study. Also, data on student's academic performance was obtained from student's scores in four selected school subjects. Data obtained was analyzed using descriptive and inferential statistical techniques; Pearson Product Moment Correlation and Multiple regression analysis (ANOVA). The results result revealed a positive and significant relationship between permissive patenting style with academic performance (p<0.05). However, no relationship exists between authoritarian parenting and demanding parenting with academic performance of students (p>0.05). Also, the result from the study identified income, educational background and occupational level as well as permissive parenting style as the main predictive variables influencing students' academic performance.